2020
DOI: 10.1126/scitranslmed.aaz3426
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes derived from Vδ2-T cells control Epstein-Barr virus–associated tumors and induce T cell antitumor immunity

Abstract: Treatment of life-threatening Epstein-Barr virus (EBV)–associated tumors remains a great challenge, especially for patients with relapsed or refractory disease. Here, we found that exosomes derived from phosphoantigen-expanded Vδ2-T cells (Vδ2-T-Exos) contained death-inducing ligands (FasL and TRAIL), an activating receptor for natural killer (NK) cells (NKG2D), immunostimulatory ligands (CD80 and CD86), and antigen-presenting molecules (MHC class I and II). Vδ2-T-Exos targeted and efficiently killed EBV-assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 66 publications
0
65
0
Order By: Relevance
“…For example, miRNA-sponges or anti-miRNA oligonucleotide therapeutic 'antagomirs' have been utilized to effectively suppress EBV-driven tumors [176,239]. A new technology is 'exosome-based therapy' with loaded immunostimulatory cargo as cell-free immunotherapy for EBV-associated malignancies [240]. The tumor-suppressive role for other miRNAs (miR-216b) through inhibition of KRAS-related AKT and ERK signaling has also been shown in NPC as a proof of concept [241].…”
Section: Clinical Potential Of Mirnas and Other Non-coding Rnasmentioning
confidence: 99%
“…For example, miRNA-sponges or anti-miRNA oligonucleotide therapeutic 'antagomirs' have been utilized to effectively suppress EBV-driven tumors [176,239]. A new technology is 'exosome-based therapy' with loaded immunostimulatory cargo as cell-free immunotherapy for EBV-associated malignancies [240]. The tumor-suppressive role for other miRNAs (miR-216b) through inhibition of KRAS-related AKT and ERK signaling has also been shown in NPC as a proof of concept [241].…”
Section: Clinical Potential Of Mirnas and Other Non-coding Rnasmentioning
confidence: 99%
“…In addition, natural killer (NK) cell–derived exosomes exert cytotoxic effects on tumor cells by delivering functional NK proteins, namely, FasL and perforin ( 5 8 ). Moreover, exosomes derived from γδ2-T cells contain death-inducing ligands [FasL and TRAIL (TNF related apoptosis inducing ligand)], which target and efficiently kill Epstein-Barr virus–associated tumor cells ( 9 ). Previous studies have used neutrophil-derived EVs to treat arthritis and sepsis ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, targeting EBV + exosomes is considered as a promising new treatment for EBV + tumors. Wang et al ( 120 ) found that exosomes derived from phosphoantigen-expanded Vδ2-T (Vδ2-T-Exos) cells could promotes EBV antigen-specific CD4 and CD8 T cell expansion and kill EBV-associated tumor cells through FasL/TNF-related apoptosis-inducing ligand pathways. These findings suggested a strategy for the treatment of EBV-associated tumors using Vδ2-T-Exos.…”
Section: Future Perspectives: Exosomes Could Be Utilized As a New Therapeutic Methodsmentioning
confidence: 99%